Digital ethnography of home use of digital personal assistants. Issue 4 (12th March 2022) - Paay, Jeni; Kjeldskov, Jesper; Hansen, Kathrine Maja; Jørgensen, Tobias; Overgaard, Katrine Leth
ABSTRACT: Commercialised voice user interface devices for the home, like Amazon Echo, Google Home, and Apple HomePod, with integrated digital personal assistants have rapidly grown in popularity. These devices embody intelligent software agents that support users in their everyday life through easy and intuitive conversational interactions. While their use in everyday activities is largely unexplored, the proliferation in home use presents a valuable opportunity to add to understanding around the use of in-home digital personal assistants. In this paper, we investigate their home use in a broad context to learn more about people's experiences, attitudes, interactions and expectations with these devices contributing new insights to current knowledge around this use. Applying the digital ethnography method, we collected 3542 reviews and comments about Amazon Echo, Google Home, and Apple HomePod on Amazon, eBay, and Reddit. Six main themes and 29 categories were derived through filtering, thematic analysis and affinity diagramming. These findings constitute a conceptual framework characterising the current landscape of home use of digital personal assistants. Additionally, we identify and discuss unique issues discovered around the invisible interface, interactive freedom, and creative appropriation. We use our findings to propose implications for interaction design of DPAs for home use.